MODERN METHODS OF LABORATORY DIAGNOSTICS (International Conference on Economics, Finance, Banking and Management, 2025)
Laboratory diagnostics plays a key role in modern medicine, providing more than 70% of the information needed for diagnosis, monitoring the course of diseases and assessing the effectiveness of therapy. Modern technologies are rapidly evolving, expanding the possibilities of diagnostics and increasing its accuracy, specificity and speed. This article discusses the main directions of laboratory diagnostics development, including molecular genetic methods, high-throughput sequencing, immunochemical technologies, process automation and the integration of artificial intelligence [1,2,3,4].